Public Policy or Government Programs: Are a Contribution to the Inclusion in Chile? - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
Given the importance of Public Policies for social transformation, the document explains why and under what circumstances they constitute a decisive factor to promote or inhibit social transformation. A policy is a purposeful, intentional, planned behavior, not just reactive, casual. It is set in motion with the decision to achieve certain objectives through certain means: it is an action with meaning. It is a process, a course of action that involves a whole complex set of decisions and operators . Politics is also a public communication activity . Hence, the purpose of this article is s be a guide in the understanding and analysis of what is meant by Public Policies, as well as contributing to the understanding of the mechanisms for their design and elaboration. That they have a clear and simple idea of ​​what Public Policies are in a generalized context and the steps that must be carried out to implement them.